Analysis of Biogeophysics Characteristics and Discharge of Lompo Riaja Atas River and Lompo Riaja Bawah River, Ralla Sub Watershed - Usman Arsyad; Beta Putranto; Nur Aeni; Wahyudi Isnan; Hasnawir (Jurnal Penelitian Kehutanan Wallacea, 2019)
The biogeophysical characteristics of watersheds have an important role as a determinant of the river discharge amount in the watershed. Various watershed problems such as flood and drought related to river discharge require data and information. The importance of this data and information will determine a better watershed management plan. The issue of flooding and drought are the important issues in Ralla subwatershed, Souht Sulawesi Province. This study aims to describe the biogeophysical characteristics and the discharge of Lompo Riaja Atas and Lompo Riaja Bawah Rivers in Ralla subwatershed, Lisu Watershed. This research was conducted in from November 2016 to August 2017. Primary data collection was done through river discharge and precipitation measurements during 34 days of observation. Secondary data obtained from government or related agencies such as geological data obtained from Geological map of the Ujung Pandang sheet 1982, the slope data from Aster DEM, land type from RePPProt 1987, land cover data from google earth image 2015. A quantitative descriptive method was used to analyze the data obtained. The results showed that the Lompo Riaja Atas and Lompo Riaja Bawah rivers have relatively similar discharge fluctuation, although they have a different amount of discharge. River discharge of both rivers is more influenced by rainfall compared to biogeophysical conditions such as geology, topography, soil type, watershed area, watershed shape, river length and order, gradient, flow pattern, flow density,and land cover.